Role of location of household and its socio-economic status on energy consumption dynamics in rural Nepal: a categorical data analysis - Jyoti U. Devkota (Institute of Advanced Engineering and Science, 2020)
This study is based on data collected from two sample surveys. They are namely survey of 300 households of national grid energy users and 400 households of biogas users. It was conducted in three different rural settings of Nepal. The responses to questions were classified into multiple choice options. This generated categorical data and reduced ambiguity and confusion between interviewer and interviewee. Such data were classified into ordinal scale and modelled. As the dependent variable had more than two categories, polytomous and not dichotomous models are developed and fitted. Ten different hypotheses assessing and measuring the energy consumption dynamics are tested. Values of parameters of these model and odds ratio are used in quantifying the impact of change with respect to energy consumption. The variables considered were namely time spent in the collection of firewood, type of house, amount of firewood saved, time saved, employer and school located within 15 min distance. Such data based studies are very crucial for country like Nepal which lacks a strong backbone of accurate and regularly updated official records. They can be generalized to other counties of Asia and Africa. Such results provide guidelines to policy makers and planners regarding formulation of realistic energy policies for such countries.